Erythrocyte Magnesium Levels in type I and type II Iraq diabetic patients effect of antidiabetic treatment - Kazaa, Faris Abdul Kareeml; Abdulaziz, Lewai S.; Naji, Ragad I. (AL-Kindy College Medical Journal, 2012)
Background: Direct measurement of intracellular magnesium using erythrocytes has been suggested as a sensitive indicator for the estimation of body magnesium store. Marked depletion in plasma and erythrocyte magnesium levels was particularly evident in diabetic patients with advanced retinopathy and poor diabetic control. While insulin has been shown to stimulate erythrocyte magnesium uptake, hyperglycemia per se suppressed intracellular magnesium in normal human red cells.Aim of the study: To investigate the erythrocyte magnesium level in Iraqi type I and II diabetic patients, with specific emphasis on the effect of both, metabolic control and the type of antidiabetic treatments.Methods: Sixty two diabetic patients (7 with type I and 55 with type II diabetes mellitus) recruited from the outpatient diabetes clinic at the Specialized Center For Endocrine Diseases-Baghdad, during the period from 1st October 2005 to 28th February 2006. Eighteen non-diabetic normomagnesemic healthy controls matched for age and sex were participated in this study. Of the diabetics, 22 were using insulin (7 with type I and 15 with type II diabetes mellitus), 40 were taking oral antidiabetic agents (All with type II diabetes mellitus) and none were using both. Serum and erythrocyte magnesium concentration were measured for both groups, and Glycated hemoglobin levels were estimated only for diabetics.Results : Mean serum and erythrocyte magnesium levels were significantly (p